A comparative transcription map of the murine bare patches (Bpa) and striated (Str) critical regions and human Xq28. - Levin, M L; Chatterjee, A; Pragliola, A; Worley, K C; Wehnert, M; Zhuchenko, O; Smith, R F; Lee, C C; Herman, G E

(untitled) (Genome Research, 1996)
The X-linked developmental mouse mutations bare patches (Bpa) and striated (Str) may be homologous to human X-linked dominant chondrodysplasia punctata (CDPX2) and incontinentia pigmenti (IP2), respectively, based on their genetic mapping and clinical phenotypes. Bpa and Str have been localized to an overlapping critical region of 600 kb that demonstrates conserved gene order with loci in human Xq28 between DXS1104 and DXS52. As part of efforts to isolate the genes involved in these disorders, we have begun to develop a comparative transcription map spanning this region in both species. Using techniques of cross-species conservation and hybridization, exon trapping, and cDNA selection we have identified four known genes or members of gene families--caltractin, a member of the gamma-aminobutyric acid (GABAA) receptor gene family, a member of the melanoma antigen gene (MAGE) family, and several members of the murine-specific, X-linked lymphocyte regulated gene (Xlr3) family. Trapped exons and, in some cases, longer cDNAs have been isolated for potentially 7-9 additional genes. One cDNA demonstrates highly significant homology with members of the Krüppel family of zinc finger transcription factors. A second novel cDNA demonstrates homology at the 3' end of the predicted amino acid sequence to a LIM domain consensus. Gene order appears conserved among those cDNAs determined to be present in both human and mouse. Three of the murine transcripts appear to be present in multiple copies within the Bpa/Str critical region and could be associated with a predisposition to genomic rearrangements. Reverse transcriptase PCR (RT-PCR) and Northern analysis demonstrate that several of the transcripts are expressed in mid-gestation murine embryos and neonatal skin, making them candidates for the Bpa and Str mutations and their respective homologous human disorders.